UNIVERSITY STUDENTS' PERCEPTION OF PAKATAN HARAPAN'S 14TH GENERAL ELECTION MANIFESTO - Zawiyah Mohd Zain; Noor Faizzah Dollah; Halimah Abdul Manaf (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2025)
In the 14th general election (GE14), for the first time, the opposition party (Pakatan Harapan) defeated the Barisan Nasional party, which had been ruling for 61 years. The victory was largely attributed to their manifesto that promised several changes. However, the implementation of the manifesto faced several constraints. This article aims to explore the perception of students from Public Institutions of Higher Learning (IPTA), namely Universiti Utara Malaysia (UUM) and Universiti Malaysia Perlis (UNIMAP) towards the formation and implementation of the manifesto. The study used the quantitative method and included 410 respondents from UUM and UNIMAP. The findings revealed that Pakatan Harapan offered attractive promises to gain community support, including their 100-day promise. The majority of respondents agreed that the Pakatan Harapan manifesto was made in haste, merely to win votes without considering its feasibility. This was evident when many of the promises could not be fulfilled even after PH ruled for more than a year, and their popularity plummeted in 2019 when they lost a few by-elections. In the 15th General Election (GE15), Pakatan Harapan returned to power by winning the most seats in parliament and forming a unity government with the support of other parties. Compared to the GE14 manifesto, the manifesto offered by PH in GE15 is more realistic, focusing on crucial aspects that are expected to be implemented well.